Ahmadiyah School, Qodyani Movement and its Problems in Indonesia: A Critical Reflection on Religion, State and Society - Herdi Sahrasad; Hendra Hendra; Arizal Joko (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study examines how the Ahmadiyah Qadiani minority in Indonesia has sought to preserve its existence and ensure cadre regeneration amid persistent discrimination, persecution, and social exclusion during the post-Reform era. Using a qualitative approach based on observations, documentation, and semi-structured interviews, the research focuses on the Arif Rahman Hakim (ARH) Islamic Boarding School in Tangerang as a case study. The findings reveal that the school functions as a strategic institution for transmitting Ahmadiyah beliefs and values through a dual curriculum consisting of general Islamic studies and specialized Ahmadiyah teachings. This educational model aims to strengthen the intellectual, emotional, and ideological development of Ahmadiyah youth while fostering a strong collective identity within the community. Although ARH is not directly administered by the Ahmadiyah Nizam, it serves as an important center for preparing future generations of Ahmadiyah members. The study also notes that the institution operates in a sensitive legal and religious context, as the Indonesian Ulema Council (MUI) has declared Ahmadiyah Qadiani a deviant sect in its 1980 and 2005 fatwas. Therefore, the research concludes that government policies toward Ahmadiyah educational institutions should prioritize prudence, fairness, and the prevention of violence while safeguarding social harmony and the rule of law.